2003
DOI: 10.1053/jhep.2003.50295
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Potentiates Hepatitis C Virus Replicon Expression

Abstract: H epatitis C virus (HCV) is responsible for the vast majority of cases of transfusion-associated and community-acquired non-A, non-B hepatitis 1,2 and infects an estimated 170 million people worldwide. 3 The seroprevalence of anti-HCV antibody in the United States has been estimated at 1.8%, which corresponds to approximately 4 million people. 4 HCV is the leading cause of chronic viral hepatitis in the United States, 5 and HCV-infected individuals are the major recipients of liver transplantation. HCV, first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
71
2
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(82 citation statements)
references
References 53 publications
8
71
2
1
Order By: Relevance
“…These cells were maintained in DulbeccoЈs Modified EagleЈs Medium (DMEM) (Gibco-BRL, Grand Island, NY) as previously described. 20 For all experiments, functionally endotoxin-free media and reagents were used. All cell cultures were checked for mycoplasma contamination by MycoAlert Mycoplasma Detection Kit (Cambrex).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…These cells were maintained in DulbeccoЈs Modified EagleЈs Medium (DMEM) (Gibco-BRL, Grand Island, NY) as previously described. 20 For all experiments, functionally endotoxin-free media and reagents were used. All cell cultures were checked for mycoplasma contamination by MycoAlert Mycoplasma Detection Kit (Cambrex).…”
Section: Methodsmentioning
confidence: 99%
“…Luciferase activities in cell lysates were quantified using a Luciferase Assay System (Promega) and a TD-20/20 Luminometer (Turner Designs, Inc., Sunnyvale, CA). 20 The results were presented as relative light units (RLU) normalized by the total proteins in the cell lysates. For IFN-␣ promoter-luciferase reporter experiments, the transfection was performed in 24-well plates, in which each well contained 10 5 cells in 1 mL DMEM.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Excess of liver fats can cause cirrhosis to liver failure. Risk factors for obesity include behavioural components which include exercise and weight control measures, social components which includes food choices and eating patterns in different cultural groups [18]. In our study two parameters vegetarian and non-vegetarian diet (at least 3 meals in a week) were investigated and it was found that diet especially non vegetarian diet could be a risk factor for various diseases as the relative risk value is greater than 1 however more data is required as this value is not statistically significant except for dermal diseases which is >0.05 does not play a significant role in diseases considered.…”
Section: Discussionmentioning
confidence: 99%
“…HCV also increases COX-2 expression; thus, this common pathway can amplify liver damage. Furthermore, toxic effects of alcohol on mitochondrial function may inhibit cellular regeneration in the live 13,14 , and HCV core proteins can also cause mitochondrial damage through free oxygen radical generation 15 .Incrased viral replication: Some in vitro hepatocyte studies have demonstrated an increase in HCV replication with alcohol exposure 16,17 , although this effect has not been demonstrated clearly in humans. Indeed, a meta-analysis performed in 2005 reported no increase in HCV RNA levels in the blood of patients with chronic alcohol consumption 18 .…”
Section: Introductionmentioning
confidence: 99%